Preventing sensory and motor dysfunctions in children receiving neurotoxic chemotherapy: PrepAir study - an update - Céline Hammadou; Bianca Celine Schmidli; Christina Schindera; Nicolas von der Weid; Uta Tacke; Oliver Faude; Sarah Koch; Fiona Streckmann (Current Issues in Sport Science)
Introduction Thanks to modern therapy, the survival rate for children with cancer is constantly improving. However, the strong treatment with chemotherapy also takes its toll. It leads to delays in motor milestones (e.g. running, climbing), which limits social reintegration as well as quality of life (Bjornard et al. 2018). Peripheral neuropathy (CIPN) is a common side effect of chemotherapy and a crucial cause of many functional disorders. It causes severe symptoms such as loss of sensation, pain, numbness, absent reflexes as well as loss of balance control. Depending on the neurotoxic agent, 52-100% of children are affected by CIPN (Kandula et al. 2016). We hypothesize that CIPN plays a crucial role for childrens well-being and reintegration and its prevention is of utmost importance. The PrepAir study therefore investigates the potential of preventive sensorimotor training to prevent CIPN. The aim is to preserve relevant sensory and motor functions in children so that they receive their planned medical therapy and become fitter and more socially integrated survivors.